Effect of magnesium chloride concentration on soymilk coagulation mechanism. (October 2021) - Lu, Yuhao; Cui, Zebang; Guan, Xiangfei; Lin, Junyuan; Zhong, Xuequn; Zhang, Minlian
Abstract: Brine tofu has been in use in China for more than two thousand years now; however, the underlying soymilk coagulation mechanism is not yet clear. In this study, we aimed to systematically investigate the effect of magnesium chloride on the mechanism of tofu preparation using the methods of composition-performance-micro-mechanism analysis, combined with droplet experiment and mercury intrusion method. With increasing magnesium chloride concentration, soymilk went through five stages, viz. no coagulation stage (0–3 mmol/L), coagulation formation stage (3–8 mmol/L), coagulation stability stage (8–50 mmol/L), coagulation dissociation stage (50–210 mmol/L), and no coagulation stage again (≥210 mmol/L). The soymilk follows a trend of diffusion, diffusion/fixation, fixation, growth, and dissolution in the droplets with increasing magnesium chloride concentration. In the coagulation stability stage, the microstructure of tofu (coagulated soymilk) alternated between loose and dense structures. In the coagulation dissociation stage, with increasing magnesium chloride concentration, the sequence of coagulation dissociation was as follows: dissociation of small pores, dissociation of macropores, dissociation of skeletons into clusters, and finally dissociation of clusters. The current study provided theoretical guidance for parameter selection and problem solving in brine tofu production process. Highlights: The MgCl2 concentration in the research was from 0 to saturation. Soymilk underwent five different stages of coagulation based on MgCl2 concentration. Dissociation was in the order: micropores, macropores, skeletons, and clusters. The trend is diffusion, diffusion/fixation, fixation, growth, and dissolution in the droplets.